Geochronology and implication of oxygen isotopic data for ongonites from Ongon Khairkhan, Mongolia - Jaroslav Dostal; Gerel Ochir (Geological Issues, 2023)
The inferred primary δ18O (+6 to +7‰) and Pb isotopic values for ongonite from Ongon Khairkhan. Central Mongolia, are consistent with a granitic parent magma and interaction with orthomagmatic fluids. The ongonites and constituent minerals record (1) an extensive and protracted crystal fractionation history, in part due to the presence of volatiles (particularly F) which depressed the solidus temperature of the felsic rocks and extended its duration of crystallization and (2) subsolidus exchange with fluids which includes late flux of heated meteoric water as indicated by modified whole rock δ18O values (+0.5 to +2.7‰). The interaction of the ongonites with internally derived orthomagmatic fluids is considered to result in enrichment and/or redistribution of several incompatible elements, but not to have greatly modified their original major element chemistry which indicates that this suite represents the last stages of fractionation of a highly differentiated, F-rich granitic magma. Late stage magmatic, water-rich fluids enriched in incompatible elements including Nb, Ta, Sn and W were responsible for die late- to post-magmatic alteration and associated W mineralization. The results of 40Ar/39Ar dating on two dyke rocks provide an age of 123 ± 1 Ma.